Analisis Instrumen Validasi Model Pembelajaran FLIP-LOCAL untuk Meningkatkan Kreativitas dan Kemandirian Siswa - Sabat, Dian Ristiani; Tika, I Nyoman; Artawan, I Putu (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop and analyze the validity of the FLIP-LOCAL learning model in enhancing students’ creativity and independence. The research employs a quantitative descriptive method, specifically a Research and Development (R&D) approach, focusing on content validity and construct validity, involving two education experts. The model was validated by experts to assess the clarity of its syntax, social system, reaction principles, and effectiveness in learning. The validation results indicate that the FLIP-LOCAL syntax consists of five main stages: preparation, exploration, elaboration, presentation, and evaluation, which are considered systematic and supportive of local potential-based learning. The social system of this model promotes active interaction between teachers and students, while the reaction principles emphasize reflective feedback, despite differences in perception among the validators. The analysis was conducted using Aikenâ€™s V formula and Lawsheâ€™s Content Validity Ratio (CVR), and overall, the model was rated as valid/highly valid with a total score of 58. The FLIP-LOCAL model integrates the flipped classroom approach and Project-Based Learning (PjBL) to enhance student engagement in more independent and creative learning.